Phospholipase C-beta 1 knockout mice exhibit endophenotypes modeling schizophrenia which are rescued by environmental enrichment and clozapine administration - McOmish, C. E.; Burrows, E.; Howard, M.; Scarr, E.; Kim, D.; Shin, H-S; Dean, B.; van den Buuse, M.; Hannan, A. J. (NATURE PUBLISHING GROUP, 2008)
Phospholipase C-beta 1 (PLC-beta 1) is a rate-limiting enzyme implicated in postnatal-cortical development and neuronal plasticity. PLC-beta 1 transduces intracellular signals from specific muscarinic, glutamate and serotonin receptors, all of which have been implicated in the pathogenesis of schizophrenia. Here, we present data to show that PLC-beta 1 knockout mice display locomotor hyperactivity, sensorimotor gating deficits as well as cognitive impairment. These changes in behavior are regarded as endophenotypes homologous to schizophrenia-like symptoms in rodents. Importantly, the locomotor hyperactivity and sensorimotor gating deficits in PLC-beta 1 knockout mice are subject to beneficial modulation by environmental enrichment. Furthermore, clozapine but not haloperidol (atypical and typical antipsychotics, respectively) rescues the sensorimotor gating deficit in these animals, suggesting selective predictive validity. We also demonstrate a relationship between the beneficial effects of environmental enrichment and levels of M1/M4 muscarinic acetylcholine receptor binding in the neocortex and hippocampus. Thus we have demonstrated a novel mouse model, displaying disruption of multiple postsynaptic signals implicated in the pathogenesis of schizophrenia, a relevant behavioral phenotype and associated gene-environment interactions.
Keywords: MUSCARINIC ACETYLCHOLINE-RECEPTOR; BRAIN CORTICAL MEMBRANES; SUPERIOR TEMPORAL CORTEX; WORKING-MEMORY DEFICITS; ACOUSTIC STARTLE REFLEX; PREPULSE INHIBITION; NEUROTRANSMITTER RECEPTORS; GLUTAMATE RECEPTORS; ANTIPSYCHOTIC-DRUGS; PREFRONTAL CORTEX